The Relationship between Technological Capability and Manufacturing Performance - Ahmad, Nurazwa; Mad Lazim, Halim; Shamsuddin, Alina; Wahab, Eta; Abu Seman, Noor Aslinda (ExcelingTech, 2019)
Technological capability plays an important role in achieving competitive advantages. It also increases performance of firms, industries, and as well as for the countries. Its’ potential as competitive weapon has been recognized to the industry. Manufacturers are striving to outperform the competitors. They are not only competing on the profit made but also struggling to perform a high level operational performance. Traditionally, manufacturers’ performance were measured based on the accounting management measures. However, the focus had shifted from solely emphasizing on financial measures to more specific multidimensional operational priorities. Hence, the purpose of this study is to investigate the relationship between two dimensions of technological capability (i.e. acquiring and upgrading) and four dimensions of manufacturing performance (i.e. quality, cost, delivery and flexibility). Stratified random sampling was employed and 302 questionnaires were distributed to the respondents ranging from small to large manufacturing firms in Malaysia. Pearson correlation analysis was employed to test the hypothesis. The study result shows that the relationship between technological capability and manufacturing performance is significant and positive. This study proved there is a connection between the variables. Further investigation is required to understand the impact of technological capability on manufacturing performance and to understand deeper the influences of differences by size of firms and industry characteristics.